2017
DOI: 10.1016/j.ajog.2017.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Are amniotic fluid neutrophils in women with intraamniotic infection and/or inflammation of fetal or maternal origin?

Abstract: Background Neutrophils are the most abundant white blood cells found in the amniotic cavity of women with intra-amniotic infection and/or inflammation. The current belief is that these neutrophils are of fetal origin. However, abundant neutrophils have been found in the amniotic fluid of women with a severe acute maternal inflammatory response but without a fetal inflammatory response in the placenta, suggesting that these innate immune cells can also be of maternal origin or a mixture of both fetal and matern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
102
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 102 publications
(105 citation statements)
references
References 123 publications
3
102
0
Order By: Relevance
“…Previous observations 67, 119 make us suggest that amniotic fluid B cells may be of fetal origin. Fetal pro/pre-B cells can be detected in the omentum as early as 8 weeks of gestation and B-cells can be detected in the liver and spleen at 12 weeks 151 .…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…Previous observations 67, 119 make us suggest that amniotic fluid B cells may be of fetal origin. Fetal pro/pre-B cells can be detected in the omentum as early as 8 weeks of gestation and B-cells can be detected in the liver and spleen at 12 weeks 151 .…”
Section: Discussionmentioning
confidence: 78%
“…Previous studies have shown that intra-amniotic infection is characterized by the infiltration of neutrophils and monocytes/macrophages 23, 27, 6769, 129132 . It was recently suggested that amniotic fluid ILCs were also implicated in regulating intra-amniotic infection and inflammation in preterm gestations 119 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations